2022
DOI: 10.3390/insects13060520
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Wingbeat Frequency of Different Taxa of Migratory Insects in Northeast Asia

Abstract: The ability to migrate is an important biological trait of insects, and wingbeat frequency (WBF) is a key factor influencing migratory behavior. The WBF of insects has been shown to be species-specific in previous studies; however, there is scant information on variations in WBF among different taxa of migratory insects. In 2018 and 2019, we investigated the relationship between WBF and 12 morphological variables (e.g., body mass, body length, total wing area, etc.) of the main migratory insects (77 species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…If C is the same dimensionless function value for all animals, we obtain by ignoring the minor variations of air density and gravitational field strength the following simple proportional relationship for the wing-beat frequency of a hovering animal [ 38 ] The functional form of Eq 6 follows from laws of physics. This mean that other power-law functions discussed in Ref.…”
Section: A Theoretically Derived Simple Expression For the Wing-beat ...mentioning
confidence: 99%
“…If C is the same dimensionless function value for all animals, we obtain by ignoring the minor variations of air density and gravitational field strength the following simple proportional relationship for the wing-beat frequency of a hovering animal [ 38 ] The functional form of Eq 6 follows from laws of physics. This mean that other power-law functions discussed in Ref.…”
Section: A Theoretically Derived Simple Expression For the Wing-beat ...mentioning
confidence: 99%
“…The wingbeat frequency of oversea migrants varies at the order, family, and species levels, which is related to the different body structures of insects [ 28 , 29 ]. Laboratory measurement results showed that the wingbeat frequency of Lepidoptera was 6.71–81.28 Hz, that of Neuroptera was 19.17–30.53 Hz, and that of Odonata was 18.35–38.01 Hz [ 29 ].…”
Section: Changes In Biological Characteristics During Insect Migrationmentioning
confidence: 99%
“…The wingbeat frequency of oversea migrants varies at the order, family, and species levels, which is related to the different body structures of insects [ 28 , 29 ]. Laboratory measurement results showed that the wingbeat frequency of Lepidoptera was 6.71–81.28 Hz, that of Neuroptera was 19.17–30.53 Hz, and that of Odonata was 18.35–38.01 Hz [ 29 ]. While Lepidoptera have a wide range of wingbeat frequencies, the wingbeat frequency of Noctuidae pests is mainly concentrated at 35–45 Hz, and temperature is the main environmental factor affecting it.…”
Section: Changes In Biological Characteristics During Insect Migrationmentioning
confidence: 99%
“…Wingbeat frequency, a parameter that plays a role in various biological and ecological functions, including mating and thermoregulation [56][57][58][59][60][61][62], is one of the main features used for clustering. The accurate interpretation and utilization of wingbeat frequency data are contingent upon a comprehensive understanding of its dependency on environmental factors, most notably temperature.…”
Section: Introductionmentioning
confidence: 99%